Die opleidingsfunksie van die geregistreerde verpleegkundige - Deel 1 - M.C. Bezuidenhout (AOSIS, 1992)
A descriptive exploratory survey was undertaken by means of a questionnaire submitted to student nurses and registered nurses of hospitals affiliated with a nursing college in the Transvaal. The aim of the study was to establish whether, and to what extent, the training function of the ward sister is realised in practice. Analysis of the data showed the ward sister to be aware of her training function and her responsibility towards the student nurse as learner. It appears that the ward sister believes herself to be adequately involved with the basic care of patients and making a significant contribution to the training of student nurses. However, the observations and the experience of the student nurse differ from this point of view. She is of the opinion that more can be done in the ward to help her achieve her training needs. The fact that in many cases she is primarily considered as a worker, comes as a great disappointment.